Monkeypox virus (MPXV) isolation from longitudinal samples of 11 patients to infer risk of onwards transmission - Dr Helen Callaby; Dr Janie Olver; Ms Kirsty Emery; Dr Kevin Richards; Dr Marian Killip; Dr Natalie Groves; Dr Jake Dunning; Professor Malcolm G Semple; Professor J Kenneth Baillie; Dr Tommy Rampling; Dr Catherine F Houlihan (International Journal of Infectious Diseases)
Introduction: Monkeypox virus (MPXV), a DNA virus in the genus Orthopoxvirus, causes the clinical disease mpox. Human-to-human transmission occurs, primarily through contact with infectious lesions. The cycle threshold (Ct) value at which mpox virus can be isolated varies in the literature. Clarification of a Ct that correlates reliably with MPXV infectivity would have significant implications for infection control measures. Persistent viral shedding of mpox is widely reported but what is less well described is the duration of infectious MPXV from patient samples, using virus isolation as proxy. Methods: This is a retrospective study using 169 longitudinal stored clinical isolates from 11 patients with clade II mpox. The samples were inoculated into African green monkey kidney (Vero E6) cells, termed passage 1 (P1). The P1 cultures were incubated and monitored for cytopathic effects (CPE). Cultures were sampled on day 0 and 7 and underwent virus inactivation, nucleic acid extraction and MPXV-specific PCR to support CPE observations. A decrease in mean MPXV Ct values from day 0 to 7 correlates to an increase in MPXV nucleic acid production, indicative of MPXV replication. Results: The sampling frame for these patients ranged from the swab of an asymptomatic contact 13 days prior to the onset of symptoms, to 109 days post the onset of symptoms. 98 samples had a detectable Ct on MPXV PCR at day 0 (Ct range 20.1 to 39.7) and virus was able to be isolated from 46.9% of these samples (46/98). The cycle threshold at which virus was able to be isolated ranged from 22.3 to 37.7. Median MPXV Ct value for which virus could be isolated was 30.7. The longest duration from MPXV culture positivity from diagnosis was 109 days, from a throat swab with a Ct value of 35.9. The sample was from a 40-50 year old man with poorly controlled HIV CD4+ T-lymphocyte count 57 cells/mm3. HIV viral load 52,800 copies/ML) who presented with an ulcerating rash affecting limbs and a necrotic tongue lesion. The median time from mpox diagnosis to culture negative was 11.5 days (range 2 to 109). Discussion: The duration of the infectious period of MPXV during clinical mpox is currently unclear with a paucity of robust longitudinal culture data, particularly from hospitalised patients. The median time of isolation of 11.5 days would fit within the known threshold but was far exceeded in a single immunocompromised patient at 109 days. Conclusion: MPXV was isolated at higher Ct values than the previously reported, potentially removing the reassurance of lack of “infectiousness” in a patient with a rising Ct on PCR. Immunocompromised patients may be infectious with MPXV for longer than those with a competent immune system and these patients may require longer isolation.